Pelatihan dan Pendampingan Sistem Informasi Berbasis Web Pada UMKM Bank Sampah Mandiri Sandubaya Selong - Nurhidayati; Muhammad Saiful; Hariman Bahtiar; Amri Muliawan Nur; Amir Bagja; Aswian Editri (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The digitalization era requires Micro, Small, and Medium Enterprises (MSMEs) to adapt through the utilization of information technology. Bank Sampah Mandiri Sandubaya, as an MSME engaged in both environmental management and community empowerment, had previously relied only on social media for promotion and information dissemination. However, this approach was insufficient to provide structured, credible, and well-documented information. This community service program aimed to develop an official website for Bank Sampah Mandiri Sandubaya and provide training and mentoring for its operators. The method employed a participatory approach through socialization, discussion, training, and evaluation. The results show that the website was successfully developed and operated by the partner’s staff. The website not only serves as a medium for promotion and information but also enhances professionalism in operational management and activity documentation. Thus, the website is expected to expand market reach, increase competitiveness, and support the sustainability of environment-based MSMEs.